2022
DOI: 10.1002/cta.3287
|View full text |Cite
|
Sign up to set email alerts
|

A ternary memristor full adder based on literal operation and module operation

Abstract: A ternary memristor full adder is designed based on the literal operation and module‐3 plus operation. Literal operation and module‐3 plus operation are the important operations in the tri‐valued algebra system. Multiple‐valued logic can increase the amount of information carried by the signals and reduce the number of devices and connections. The combination of multiple‐valued logic and memristor is an exploration of new devices and new structures. The novel ternary memristor full adder owns the advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…This popularity is mostly because of its high flexibility in threshold adjustment. Other popular technologies are graphene nanoribbon FET [34,47,60,75,76] and memristor [22,23,26,63,[77][78][79][80]. A fusion of two technologies has sometimes been exploited.…”
Section: Statistical Information About Design Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…This popularity is mostly because of its high flexibility in threshold adjustment. Other popular technologies are graphene nanoribbon FET [34,47,60,75,76] and memristor [22,23,26,63,[77][78][79][80]. A fusion of two technologies has sometimes been exploited.…”
Section: Statistical Information About Design Techniquesmentioning
confidence: 99%
“…This popularity is mostly because of its high flexibility in threshold adjustment. Other popular technologies are graphene nanoribbon FET [34, 47, 60, 75, 76] and memristor [22, 23, 26, 63, 77–80]. A fusion of two technologies has sometimes been exploited. Balanced versus Unbalanced (Figure 3b): There are two ways to define ternary digits (trits) in base 3: i ) Balanced (or signed) with the number set {−1, 0, +1} 3 , and ii ) Unbalanced (or unsigned) with the number set {0, 1, 2} 3 .…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to achieve multi-value effects with traditional dual-port memristors, and it requires additional circuit consumption when designing large-scale memristor arrays. 19,20 In Zhang et al, 21 it was demonstrated that quantized current was a result of formation of tree-shaped conductive filaments inside the memristor with the SET/RSET process being controlled by the application of gate voltage. The electrical symbol of the gate-tunable memristor is shown in Figure 1A, and its approach to achieving multiple resistance states by applying different gate voltage to change its hysteresis loop is shown in Figure 1B.…”
Section: Proposed Model Of Gate-tunable Memristormentioning
confidence: 99%
“…With memristor arrays, more individual memristor resistance values enable higher quantization accuracy to be achieved. It is difficult to achieve multi‐value effects with traditional dual‐port memristors, and it requires additional circuit consumption when designing large‐scale memristor arrays 19,20 . In Zhang et al, 21 it was demonstrated that quantized current was a result of formation of tree‐shaped conductive filaments inside the memristor with the SET/RSET process being controlled by the application of gate voltage.…”
Section: Proposed Model Of Gate‐tunable Memristormentioning
confidence: 99%